UPAYA PENINGKATAN HASIL BELAJAR KIMIA MATERI SIFAT KOLIGATIF LARUTAN MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SAVI - JAINURU (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The purpose of this study was to determine the improvement of the chemical learning outcomes of the colligative properties of the solution through the application of the cooperative learning model SAVI type in class XII IPA 2 students of Senior High school 2 Baubau in the 2019/2020 academic year. This research is a classroom action research. The subjects of this study were students of class XII IPA 2 Senior High school 2 Baubau. This research was conducted from September to October 2019The results showed that the results of the acquisition in the first cycle with the percentage of completeness of 67.7% of the class average value of 67.5 and increased in the results of the second cycle of 96.8% with an average grade of 77.7. In these two cycles there was a significant change in activity and the acquisition of value when compared to the pre-cycle with learning completeness which only reached 38.7% and the average value was 59.4. The results of observations on the teaching and learning process showed that student activity increased during the learning process, both in cycle I and cycle II, compared to the passive and stiff atmosphere of student learning prior to classroom action. The percentage of students who were active in cycle I was 38.18% and cycle II was 61.25%. Teacher activity also increased in cycle I and cycle II in terms of the use of teaching aids with the acquisition of a percentage score of 43.75% with a sufficient category to be 81.8% in the second cycle with a good category